Pattern of reporting and practices for the management of traumatic brain injury: An overview of published literature from India (2018)
Background: Published literature regarding the demographics and mechanism of injury for traumatic brain injury (TBI) in India has not been analyzed in an organized sample. Objectives: The objective of this systematic review was to organize the published literature from India related to TBI and analyze it in a very specific sample to identify the specific patterns of injury and associated mortality. Materials and Methods: A search strategy with specific inclusion criteria was performed in PubMed, Cochrane, Web of Science, and the World Health Organisation (WHO) Global Health Library. The process included an additional search within the indexed literature and the website-based population survey reports. Results: Our review identified 72 studies from 300 potentially relevant articles based on the broad criteria that defined the demographics of the patients suffering from TBI and the details of trauma sustained, including the mechanism of injury as well as its diagnosis, management, and outcome. Changes in demographic patterns, the patterns of the body regions involved, the associated injuries, the clinical presentation, the follow-up status of patients suffering from TBI, who may or may not have shown clinical improvement, the overall outcome, as well as the mortality and disability status reported in the literature were analyzed. A high incidence of TBI in the productive population is of serious concern. Extremes of ages are more vulnerable to severe injury and a poor outcome. Conclusion: Quantitative analysis of injuries and outcomes of TBI victims shows a bigger health impact in the economically active population and in patients in the extremes of age groups.